2001
DOI: 10.1051/0004-6361:20011281
|View full text |Cite
|
Sign up to set email alerts
|

The CORALS survey I: New estimates of the number density and gas content of damped Lyman alpha systems free from dust bias

Abstract: Abstract. We present the first results from the Complete Optical and Radio Absorption Line System (CORALS) survey. We have compiled a homogeneous sample of radio-selected QSOs from the Parkes Catalogue and searched for damped Lyman alpha systems (DLAs) towards every target, irrespective of its optical magnitude. This approach circumvents selection effects -particularly from intervening dust -which have long been suspected to affect DLA surveys in optically-selected, magnitude-limited QSO samples. The CORALS da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
243
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(270 citation statements)
references
References 45 publications
25
243
2
Order By: Relevance
“…In the redshift range covered by the survey, 19 DLA systems have been discovered. Over the whole survey, we find that the number density n(z) and cosmological density of gas Ωgas have comparable values to the ones obtained by CORALS (Ellison et al 2001).…”
supporting
confidence: 76%
See 3 more Smart Citations
“…In the redshift range covered by the survey, 19 DLA systems have been discovered. Over the whole survey, we find that the number density n(z) and cosmological density of gas Ωgas have comparable values to the ones obtained by CORALS (Ellison et al 2001).…”
supporting
confidence: 76%
“…In the redshift range covered by the survey, 19 DLA systems have been discovered. Over the whole survey, we find that the number density n(z) and cosmological density of gas Ωgas have comparable values to the ones obtained by CORALS (Ellison et al 2001).However, the number densities of DLA systems n(z) in two sub-samples of equal absorption distance path defined by the magnitude of the background QSOs differ by a factor of ≈ 5. We estimate that the probability that n(z) is equal in the two sub-samples is < 0.003.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…However, several studies have shown that most DLAs are not associated with significant amounts of dust (e.g. Murphy & Liske 2004;Vladilo, Prochaska & Wolfe 2008), and DLAs towards radio-selected QSOs, which are insensitive to the presence of dust, have a similar N H I distribution to those in optically selected QSOs (Ellison et al 2001;Jorgenson et al 2006). Pontzen & Pettini (2009) find that the cosmic H I mass density may be underestimated by 3-23 per cent at z ∼ 3 due to selection biases from dust.…”
Section: Other Systematic Effects Contributing To K(n H I )mentioning
confidence: 99%